Redes e vigilância no Xingu: a reconfiguração do território ribeirinho - BAITELLO, Clara Bezerra de Menezes (Universidade Federal do Pará, 2023)
This work examines how the construction of the Belo Monte Hydroelectric Dam at Xingu River, in Altamira city, Pará state is transforming the relationship between ribeirinhos, riverine people, and their traditional territories. Before the dam, the riverine people maintained relative territorial and social-economic autonomy. Since the construction of Belo Monte, the State and private companies are abusing their power in an attempt to gain territorial control and influence local dynamics. Subsequently, land-use planning in the region is changing. Previously organized by the ribeirinhos according to their own rules and subsistence needs, the land is now regulated by new private actors, impacting and altering the nature and purpose of the communities’ traditional activities. In order to conduct this analysis, I use the dialectical method due to its ability to analyze the contradictions of the territory.